Loneliness Among Elderly: Scenarios in Malaysia and Solutions Based on the Commentaries of Risale-i Nur - Noornajihan Ja‘afar; Rezki Perdani Sawai; Shah Rizul Izyan Zulkiply; Celal Akar (International Scientific Research Association (ISC, 2024)
Non-Indexed Publication